2013
DOI: 10.1098/rspb.2012.2605
|View full text |Cite
|
Sign up to set email alerts
|

Stable reprogramming of brain transcription profiles by the early social environment in a cooperatively breeding fish

Abstract: Adult social behaviour can be persistently modified by early-life social experience. In rodents, such effects are induced by tactile maternal stimulation resulting in neuroendocrine modifications of the hypothalamicpituitary -adrenal axis involved in stress responsiveness. Whether similar long-term alterations can occur in the hypothalamic -pituitary -interrenal (HPI) axis of poikilothermic vertebrates is unknown. We compared the expression of four genes of the HPI axis in adults of the cooperatively breeding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(69 citation statements)
references
References 45 publications
1
67
0
Order By: Relevance
“…Using quantitative real‐time PCR, we showed that the expression level of the candidate genes involved in the stress response (glucocorticoid receptors, corticotropin releasing factor) was permanently altered in the brain of these fish when they reached the adult stage (Taborsky et al. ). Our results suggest that the early rearing environment can thus induce permanent reprogramming that may directly affect social behaviour in a fish, as found in mammals.…”
Section: An Organismal Evolutionary Biologist' S Journey Into the Reamentioning
confidence: 99%
“…Using quantitative real‐time PCR, we showed that the expression level of the candidate genes involved in the stress response (glucocorticoid receptors, corticotropin releasing factor) was permanently altered in the brain of these fish when they reached the adult stage (Taborsky et al. ). Our results suggest that the early rearing environment can thus induce permanent reprogramming that may directly affect social behaviour in a fish, as found in mammals.…”
Section: An Organismal Evolutionary Biologist' S Journey Into the Reamentioning
confidence: 99%
“…Influences of social conditions during early and adolescent development on adult behavior, morphology, physiology and gene expression have been described frequently (e.g., birds : Holveck, Geberzahn, & Riebel, 2011;Mariette, Cathaud, Chambon, & Vignal, 2013;Riebel, Naguib, & Gil, 2009;White, Gros-Louis, King, Papakhian, & West, 2007;fish: Arnold & Taborsky, 2010;Chapman, Ward, & Krause, 2008;Taborsky, Arnold, Junker, & Tschopp, 2012;Taborsky, Tschirren, Meunier, & Aubin-Horth, 2013;mammals: Branchi, 2009;Delville, Melloni, & Ferris, 1998;Ferris, Messenger, & Sullivan, 2005;Sachser, Hennessy, & Kaiser, 2011;Sachser, Kaiser, & Hennessy, 2013). Influences of social conditions during early and adolescent development on adult behavior, morphology, physiology and gene expression have been described frequently (e.g., birds : Holveck, Geberzahn, & Riebel, 2011;Mariette, Cathaud, Chambon, & Vignal, 2013;Riebel, Naguib, & Gil, 2009;White, Gros-Louis, King, Papakhian, & West, 2007;fish: Arnold & Taborsky, 2010;Chapman, Ward, & Krause, 2008;Taborsky, Arnold, Junker, & Tschopp, 2012;Taborsky, Tschirren, Meunier, & Aubin-Horth, 2013;mammals: Branchi, 2009;Delville, Melloni, & Ferris, 1998;Ferris, Messenger, & Sullivan, 2005;Sachser, Hennessy, & Kaiser, 2011;Sachser, Kaiser, & Hennessy, 2013).…”
Section: Developmental Psychobiologymentioning
confidence: 99%
“…Therefore, organisms should ideally remain plastic throughout their whole life. Lorenz (1935) coined the term "imprinting" for this type of learning, to point to the stability of behaviors established in the course of sensitive periods and it has been shown later that song learning, which had been named an "imprinting like process" in the early learning literature, shared almost every feature with the originally described process of sexual and filial imprinting (Bischof, 1997;ten Cate, Vos, & Mann, 1993). Lorenz (1935) coined the term "imprinting" for this type of learning, to point to the stability of behaviors established in the course of sensitive periods and it has been shown later that song learning, which had been named an "imprinting like process" in the early learning literature, shared almost every feature with the originally described process of sexual and filial imprinting (Bischof, 1997;ten Cate, Vos, & Mann, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…In vertebrates, the hypothalamus–pituitary–adrenal/interrenal (HPA/HPI) axis has been proposed as a central mechanism responsible for long‐term effects of early social experience (Arnold & Taborsky, ; Banerjee, Arterbery, Fergus, & Adkins‐Regan, ; Fischer et al, ; Francis et al, ; Liu et al, ; Nyman et al, ; Nyman, Fischer, Aubin‐Horth, & Taborsky, ; Taborsky, Tschirren, Meunier, & Aubin‐Horth, ). Hippocampal glucocorticoid receptors (GRs) are implicated in the negative feedback loop controlling glucocorticoid production, which promotes termination of the stress response (de Kloet, ).…”
Section: Introductionmentioning
confidence: 99%
“…In rat pups, gene expression of gr in the hippocampus is increased with higher quality of maternal care (Liu et al, ) resulting in more stress‐resilient individuals. Likewise, in the highly social cichlid fish Neolamprologus pulcher, individuals reared with (vs. without) brood caring group members are less neophobic (Bannier, Tebbich, & Taborsky, ) and more socially competent as juveniles (Arnold & Taborsky, ; Nyman et al, ) and adults (Taborsky et al, ) and feature a persistently altered stress gene expression in the brain (Nyman et al, , ; Taborsky et al, ). In Japanese quails, pharmacologically activating the stress response causes large‐scale changes in gene expression in adults, including hormone receptors implicated in the regulation of serotonin, somatostatin and corticotrophin‐releasing factor (Marasco et al, ).…”
Section: Introductionmentioning
confidence: 99%